PENGUKURAN KADAR FLUORIDA, NITRAT, DAN NITRIT DALAM AIR SUMUR MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-VIS - Ngibad, Khoirul (Universitas Islam Sumatera Utara, 2023)
Fluoride is beneficial to human health but its excess or lack of water is harmful to humans as well as the environment and can cause fluorosis. On the other hand, the intake of high concentrations of nitrates and nitrites can cause methemoglobinemia. This study aims to analyze fluoride, nitrate, and nitrite levels in well water around Taman District, Sidoarjo Regency. The method used in this study was UV-Vis spectrophotometry at a wavelength of 570 nm for the measurement of fluoride levels and a wavelength of 543 nm for the measurement of nitrate and nitrite cadaver. The results showed that the well water around the Taman District of Sidoarjo Regency had fluoride, nitrate, and nitrite levels in the sample of 0.23 each; 0,73; and 0.019 mg/L (well water A) and 0.18; 0,8; and 0.042 mg/L (well water B). The fluoride, nitrate, and nitrite levels still meet the quality standard (maximum level) of chemical parameters in the environmental health quality standard for water media for sanitary hygiene purposes.